Adopting environmental management systems in the South African construction industry. - Green, Jordan Mark. (My University, 2014)
ABSTRACT It is widely acknowledged that sustainable development is a global imperative in order to achieve the dual objectives of development which meets the needs of the population, whilst ensuring long term impacts on the environment are minimised and mitigated. Therefore pressure is being placed on the construction sector to implement sustainable practices during development. Studies show that construction industries vary in their environmental maturity and are affected to varying degrees by a number of drivers and barriers which influence the adoption of sustainable development practices, specifically the implementation of Environmental Management Systems (EMS) such as ISO 14001 EMS. This study conducted interviews and administered surveys with key personnel within the major construction firms in South Africa in order to determine the level of adoption of ISO 14001 EMS and the factors affecting its uptake. The key findings indicate that, although construction organisations acknowledge the sustainable development imperative, there is currently a sluggish implementation rate as a result of mainly the cost related barriers exceeding the expected benefits of implementation. Further, although the South African construction industry is supported by comprehensive and robust environmental regulations, implementation and enforcement of these regulations is weak, whilst trade associations and industry bodies are not promoting its uptake. This has resulted in a low desire by contractors to transition to environmental practices and there is no single stakeholder currently driving the green agenda in the construction sector. Although there is degree of environmental management taking place in South African construction industry currently, it has a short term focus, rather than a long term, holistic approach encompassing all principles of sustainable development.
MBA 2014
Keywords: Environmental management,Industrial management -- Environmental aspects,Construction industry.